Tantangan generasi z dalam mempertahankan identitas nasional dari fenomena #KaburAjaDulu - Luhendra, Subhan Karunia Irobi (Maliki Interdisciplinary Journal, 2025)
This research examines the #KaburAjaDulu phenomenon that is increasingly popular among Generation Z Indonesians and its impact on national identity. The #KaburAjaDulu trend represents the desire of some young Indonesians to migrate abroad for various reasons, ranging from seeking better educational and career opportunities to dissatisfaction with domestic socio-political conditions. Using a literature review approach, this study analyses various scientific publications, media articles, and digital content related to Generation Z behaviour, the phenomenon of migration, and the construction of national identity. The study also examined secondary data from previous research on social media usage trends and shifting values among the younger generation. The results show the dilemma faced by Generation Z in balancing global aspirations with a sense of attachment to national identity. The study also identifies some potential strategies that can be implemented to strengthen national identity without inhibiting Generation Z's global perspective based on models that have been successfully implemented in various countries. It is hoped that these findings can contribute to the development of policies that facilitate Generation Z to retain their national identity while facing the challenges and opportunities of globalisation.